(untitled) (Nigerian Journal of Technology, 2018)
Next Generation Network (NGN) is intended at integrating the existing heterogeneous wireless access networks in order to produce a composite network that provides users with ubiquitous broadband experience. Currently, it has been established that Long Term Evolution (LTE) network, as a backbone network, provides broadband capacity with high efficiency, reduced latency and improved resource provisioning. Resource provisioning on this backbone network is not without its limitation as more mobile broadband services (MBBs) are evolving and users demand for mobility is on the increase. This paper, therefore, reviewed the different integration techniques for the heterogeneous networks that use LTE network as backbone that supports mobile broadband services. http://dx.doi.org/10.4314/njt.v37i2.24